Functional Significance of Islet Amyloid Polypeptide Anti-fibrillation Compounds as a Novel Treatment for Type 2 Diabetes Management - Abioye, Raliat Oyekemi (Université d'Ottawa | University of Ottawa, 2024)
Amyloidogenic proteins and peptides have been implicated in many diseases including Alzheimer’s, Parkinson’s, Huntington’s, and even prion disease. Islet amyloid polypeptide (IAPP) is one amyloidogenic peptide that has been implicated in the prognosis of type 2 diabetes (T2D). IAPP is a hormonal peptide which functions primarily in postprandial glucose regulation. However, fibrillation renders it nonfunctional and induces β-cell dysfunction via mechanisms including oxidative stress and membrane rupture, resulting in toxicity and apoptosis. Hence, the identification of anti-fibrillation compounds is a common approach to mitigating fibrillation and fibrillation-induced β-cell toxicity. In comparison to other more popular antidiabetic targets, however, IAPP fibrillation is largely understudied as a potential treatment of T2D. Furthermore, natural compounds such as polyphenols, peptides, and polysaccharides, are not commonly considered as antidiabetic agents. Thus, this thesis seeks to expand the known anti-fibrillation compounds, with a special emphasis on structure-activity relationships. This will enhance the understanding of important anti-fibrillation features, and pave way to the rational design or identification of novel IAPP fibrillation inhibitors. This research employed techniques to screen for potential fibrillation inhibitors using thioflavin T fluorescence kinetics. The effects of the biomolecular interactions between the identified inhibitors and IAPP on fibrillation and secondary structure were monitored using dynamic light scattering, and circular dichroism techniques. Morphological characterization of IAPP fibrils were carried out using transmission electron microscopy and fluorescence microscopy. The theoretical binding interactions between the anti-fibrillation compounds and IAPP were determined via in silico molecular docking, using monomeric and pentameric IAPP and binding models. The manifestation of the observed anti-fibrillation activity on membrane leakage and cytotoxicity was assessed using calcein-encapsulated giant unilamellar vesicles (GUVs) and rat insulinoma β-cells (RIN-m) respectively. Finally, the effect of IAPP fibrillation inhibition on β-cell functionality was evaluated by monitoring oxidative stress and glucose-stimulated insulin secretion. From this study, IAPP anti-fibrillation polyphenols caffeic acid, gallic acid, rutin, and quercetin, and peptides MANT, YMSV, and TNGQ were discovered. These compounds demonstrated significant reductions in IAPP fibrillation, average particle sizes, stabilized IAPP secondary structure, and altered the fibrillar morphology of IAPP. Docking interactions studies identified unique binding sites of each anti-fibrillation peptide to IAPP. Subsequent investigations into how domain-specific binding of peptides MANT, YMSV, and TNGQ translates to membrane-protective effects uncovered the role of cross-domain interactions by TNGQ in preventing IAPP fibrillation-induced membrane leakage and β-cell toxicity. Peptide-polyphenol interactions between rutin and MANT, YMSV, or TNGQ revealed a non-additive effect on anti-fibrillation activity. Nevertheless, rutin-TNGQ combinations demonstrated enhanced fibrillar disaggregation activity and decreased prevalence of membrane-bound toxic oligomeric species which translated to an enhanced ability to minimize β-cell oxidative stress; an effect that was not observed in the presence of rutin or TNGQ alone. Despite this, no significant effect was observed on glucose-stimulated insulin secretion. Obtained results highlighted the importance of multifunctional anti-fibrillation compounds that retain individual activity and shed a positive light on the benefits of non-additive inhibitor systems. Taken together, this work demonstrated novel perspectives in fibrillation inhibitor design, the role of IAPP cross-domain interactions in mitigating fibrillation induced β-cell dysfunction, and the importance of structure on observed anti-fibrillation activity.
Keywords: Islet Amyloid Polypeptide; Fibrillation; Bioactive Peptides; Polyphenols; Type 2 Diabetes; Pancreatic beta cells; Cytotoxicity; Biomolecular Interactions; Disaggregation; Nutraceuticals